FINANCIAL PERFORMANCE ANALYSIS BASED ON ECONOMIC VALUE ADDED (EVA) AND MARKET VALUE ADDED (MVA) (CASE STUDY ON PT. HOTEL SAHID JAYA INTERNATIONAL Tbk) - Afifah, Fatimah Azzahro (Jurnal Ilmiah Mahasiswa FEB, 2017)
This case study valuing financial performance of PT. Hotel Sahid Jaya International used economic value added (EVA) and market value analysis (MVA) as the measurement tools of finance performance, based on five years financial statement consolidation of PT. Hotel Sahid Jaya International Tbk that collected from Galeri Investasi Economic and Business Faculty of Brawijaya University that cover the financial report of hotel Sahid Jaya from all location around Indonesia. The results showed that the company's financial performance as measured by economic value added and market value added in PT. Hotel Sahid Jaya International Tbk are both positive. It indicates that the firm’s financial performance is efficient as the NOPAT score is higher than their cost of capital and the firm’s financial performance is efficient  and can give wealth value added for their shareholders. But the problem is the shareholder’s wealth value always decreases every years followed by the decrease of the share price. The result of this research can be used as a consideration for the target investor to invest their money in hotels business. For a manager, this research may help them to evaluate their firm performance and for decision making process. Keywords : Economic Value Added, Market Value Added, Financial Performance